TAMAN NASIONAL BUKIT BARISAN SELATAN SEBAGAI DESTINASI WISATA DI KABUPATEN TANGGAMUS - Wirawan, M. Yusuf; Nurikah, Nurikah; Jazuli, H.E.R (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The Bukit Barisan Selatan National Park (TNBBS) in Tanggamus Regency has tourism potential that has not been optimally managed by the local government. This study aims to analyze the efforts of the local government in managing TNBBS as a tourist destination based on Tanggamus Regency Regional Regulation No. 6 of 2019 on Integrated Tourism Development, as well as to identify the natural resources that can be developed. This research employs the theories of authority and tourism, using an empirical juridical method with a descriptive-analytical approach. Primary and secondary data were collected through interviews, observations, and documentation, then analyzed descriptively using a qualitative approach. The results indicate that the Tanggamus Regency Government has made efforts to designate tourist destinations, coordinate development, and organize tourism education, training, and research. TNBBS has several tourism potentials, including Sukaraja Waterfall, Teluk Semaka, camping grounds, Tarsius and Rafflesia observation plots, and other biodiversity. However, these efforts remain suboptimal, particularly in tourism marketing, since the primary authority for managing TNBBS lies with the Bukit Barisan Selatan National Park Agency as a conservation area. The tourism potential in this region has met several strategic tourism area aspects outlined in Article 32 of Regional Regulation No. 6 of 2019. In conclusion, although the local government has carried out part of its authority, further optimization of tourism management and marketing is still needed. Therefore, the local government is expected to be more proactive in promoting tourism to enhance the attractiveness of TNBBS in the Tanggamus area.